Extração, composição química e perfil sensorial de óleos de amêndoa de castanha de caju quebrada - Leal, Amanda Rodrigues (2024)
During the processing of cashew nuts, there is a rate of nut breakage of around 40%; therefore, the extraction of oil from these parts represents an added value to the cashew chain. This study aimed to obtain an oil extracted from lower commercial value cashew nuts, characterize the oil in terms of its chemical, physical, and sensory evaluation, and evaluate the changes throughout its storage. Oil samples were obtained from different classifications of cashew nuts and analyzed for acid and peroxide values, color, fatty acids, and volatile compounds. The sample with the best results was characterized by its physical, chemical, and sensory evaluation of the changes that occurred over 60 days of storage at 30, 40, and 50 °C (accelerated conditions). Broken nuts oils presented similar or superior quality to whole nut oil (LW3), especially samples butts (B3) and large pieces (P3), with acidity, peroxide and color values equal to LW3. Less intact nut oils had higher acid values than LW3 oil and high proportions of AGM (64.47 to 65.28%). Sample P3 presented higher ratios of volatile compounds not derived from oxidation. Therefore, the oil selected to continue the study was P, in which the presence of anacardic acids 15:3, 15:2, 15:1, and 17:3, the phytosterols β-Sitosterol, cycloartenol, anosterol, and campesterol, with oleic acid as its main fatty acid (65.24 to 66.49%). Throughout storage, there were subtle changes in the oxidative quality of the oil, mainly at 50°C, with an increase in acid and peroxide values, more significant color differences, and a reduction in polyunsaturated fatty acids. Sensory acceptance decreased over time, but at the end of storage, the samples still obtained scores above ‘like slightly’. Furthermore, the Check-All-That-Apply (CATA) test showed that the oil presented positive sensory attributes, such as yellow color, brightness, clear appearance, sweet taste, neutral flavor and cashew nut aroma. As a result, it was observed that the oil was stable throughout storage, having great potential for commercialization and consumption for direct use and in culinary preparations. This study expands the possibility of valuing cashew nuts with lower commercial value through the production of oil with adequate quality for consumption.